2006
DOI: 10.1902/jop.2006.050188
|View full text |Cite
|
Sign up to set email alerts
|

Additional Effect of Dentifrices on the Instant Efficacy of Toothbrushing

Abstract: The use of dentifrice does not contribute to the instant mechanical plaque removal during manual toothbrushing. A higher dentifrice abrasivity does not seem to contribute to increased plaque removal with a manual toothbrush. It appears that the mechanical action provided by the use of a toothbrush is the main factor in the plaque-removing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 20 publications
2
49
1
Order By: Relevance
“…1 Mechanical biofilm removal by powered toothbrushing has been demonstrated to be superior to manual brushing. 2 However, complete biofilm removal can never be achieved and after a single self-performed brushing, the amount of oral biofilm can only be reduced by 50-60%, 3,4 leaving biofilm behind at locations out of reach for mechanical removal such as fissures, buccal pits, posterior interproximal areas and gingival margins, where oral pathologies mostly develop. 5 In orthodontic patients, the number of locations out of reach of mechanical removal is even higher, making orthodontic patients more prone to oral pathologies than non-orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 Mechanical biofilm removal by powered toothbrushing has been demonstrated to be superior to manual brushing. 2 However, complete biofilm removal can never be achieved and after a single self-performed brushing, the amount of oral biofilm can only be reduced by 50-60%, 3,4 leaving biofilm behind at locations out of reach for mechanical removal such as fissures, buccal pits, posterior interproximal areas and gingival margins, where oral pathologies mostly develop. 5 In orthodontic patients, the number of locations out of reach of mechanical removal is even higher, making orthodontic patients more prone to oral pathologies than non-orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Inconclusive evidence exists in the literature with regard to the additional (beneficial) mechanical effect of a dentifrice on plaque removal. Paraskevas et al (17,18) affirm that the use of toothpaste did not contribute to mechanical plaque removal during manual toothbrushing and it seemed that the mechanical action provided by the toothbrush was the main factor in the plaque-removing process. Addy et al (19) in 80s already showed that the triclosan toothpastes containing the copolymer and chlorhexidine solution, produced significant reductions on salivary bacterial counts and to correlate it with plaque inhibitory properties of antimicrobial compounds.…”
Section: Discussionmentioning
confidence: 99%
“…• Stannous fluoride and stannous fluoride with AmF. Their main limiting factor may be tooth staining [65,129,130]. This limiting factor is not associated with formulations including SHMP.…”
Section: Safety and Adverse Effectsmentioning
confidence: 99%
“…Its main use should be the treatment of gingivitis by reaching a balance between the biofilm and the host response, thus maintaining a gingival health status. Dentifrices containing triclosan and copolymer [58,86] as well as stannous fluoride [58,130] have demonstrated antiplaque efficacy in 6-month clinical trials. The available data from the systematic reviews show the clinical benefit of its daily use when compared with the provision of oral hygiene instructions.…”
Section: Indications Of Toothpastes With Plaque Inhibitory And/or Antmentioning
confidence: 99%